Improving Appropriate Behaviour of a Student with Emotional and Behavioural Problems through SWPBS and LST Collaboration - Pujaningsih, Pujaningsih; Haryanto, Haryanto (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
Support for students with emotional and behavioural problems (EBP) in Indonesia remains limited. This action research explores the use of School-Wide Positive Behaviour Support (SWPBS) to improve student behaviour through collaboration among classroom teachers, subject teachers, special education teachers, school administrators, parents, and psychologists. The study involved 13 teachers and key school stakeholders working together as a learning support team to enhance the appropriate behaviours of a student with EBP. Data were collected through structured and informal teacher reflections and analysed using descriptive statistics. Findings show that collaborative implementation of SWPBS increased the student’s appropriate behaviours and reduced inappropriate ones. Internalising behaviours, such as staying on task and avoiding distractions, reached 100% frequency, while externalising behaviours like physical disruptions dropped to 0%. Class cooperation and routine adherence also reached 100%. However, verbal engagement remained low, with 0% participation in discussions and 33–67% in other academic behaviours, indicating the need for continued support in this area. Teachers reported using various strategies to foster a supportive classroom environment, including greeting the student (66.7%), maintaining a calm setting (40%), assisting with problem-solving (33.3%), and teaching emotional regulation (26.7%). Other strategies included adapted tasks, physical activity, leadership opportunities, and positive reinforcement. These findings highlight the effectiveness of teacher-driven, relationship-based strategies in supporting students with EBP. They also suggest implications for future educational policy, including the integration of social-emotional learning in teacher training and the inclusion of student wellbeing indicators in school practice to promote more inclusive and responsive educational environments.